1995
DOI: 10.1007/bf00222004
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the genetic effects for several traits in oil palm (Elaeis guineensis Jacq.) populations. I. Population means

Abstract: An oil palm experiment was set up in the Ivory Coast to compare the effects of crossing and selfing within two origins, Deli and La Mé, on the mean and the variability of Deli x Mé between-origin hybrids. The originality of the experiment lay in the crossing plan, which provided access to genetic parameters related to additivity, dominance and different components of epistasis. This first part covers the analysis of the components of the mean. The parents used were obtained from four palms, two from each origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2002
2002

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In self-compatible species, mating among ramets of the same genet will cause a significant portion of the non-additive effect on a trait to be passed on to seed offspring because it results in reduced breakup of allelic combinations (Baudouin et at., 1995;Pollack and Sabran, 1999). The inherently spatial nature of clonal growth may cause ramets of a resistant genet to be clumped within a population, which is likely to increase the frequency of matings among ramets of the same genet (Silander, 1985b, Charpantier, pp.…”
Section: Indirect Evolutionary Eflects Ol Genotypic Selection On Genementioning
confidence: 99%
“…In self-compatible species, mating among ramets of the same genet will cause a significant portion of the non-additive effect on a trait to be passed on to seed offspring because it results in reduced breakup of allelic combinations (Baudouin et at., 1995;Pollack and Sabran, 1999). The inherently spatial nature of clonal growth may cause ramets of a resistant genet to be clumped within a population, which is likely to increase the frequency of matings among ramets of the same genet (Silander, 1985b, Charpantier, pp.…”
Section: Indirect Evolutionary Eflects Ol Genotypic Selection On Genementioning
confidence: 99%
“…In a theoretical work on the analysis of the genetic effects of several oil palm traits, Baudouin et al (1995) concluded that "Epistasis effects may contribute substantially to population means if the material tested is highly heterozygous, the genetic base is narrow (selected material or few individuals used) or there is linkage disequilibrium (due to further selection and insufficient intercrossing generations. )", although in the papers published by Balatero et al (1995), Gingera et al (1995) and Holtom et al (1995) there was no evidence of epistasis.…”
Section: Introductionmentioning
confidence: 99%